2021
DOI: 10.3390/s21227434
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of SEPIC, Ćuk and Zeta Converters in Discontinuous Conduction Mode and Performance Evaluation

Abstract: High-order switched DC-DC converters, such as SEPIC, Ćuk and Zeta, are classic energy processing elements, which can be used in a wide variety of applications due to their capacity to step-up and/or step-down voltage characteristic. In this paper, a novel methodology for analyzing the previous converters operating in discontinuous conduction mode (DCM) is applied to obtain full-order dynamic models. The analysis is based on the fact that inductor currents have three differentiated operating sub-intervals chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Successfully operating in the discontinuous mode, without compromising the quality of the electrical energy, can be essential to reducing losses in these systems. Contribution [10] of the Special Issue carries out a performance evaluation of both modes of operation in SEPIC, Cuk, and Zeta converters.…”
Section: A Brief Review Of the Contributions In This Special Issuementioning
confidence: 99%
“…Successfully operating in the discontinuous mode, without compromising the quality of the electrical energy, can be essential to reducing losses in these systems. Contribution [10] of the Special Issue carries out a performance evaluation of both modes of operation in SEPIC, Cuk, and Zeta converters.…”
Section: A Brief Review Of the Contributions In This Special Issuementioning
confidence: 99%
“…The nonlinear model of SEPIC converter is derived using the graphical method detailed in [24], which gives…”
Section: Dynamics Of Sepic Converter In Dcmmentioning
confidence: 99%
“…All converter circuits involve capacitors, inductors, transistors, and diodes for energy storing and directing from the source side to the load side (Deepak et al, 2018;Walker and Sernia, 2004) showed an integrated comparison among converter types and highlighted the functions of the converter parameters. Based on the converter parameters, the converter can operate in either continuous conduction mode CCM, in which the minimum inductor current will be more than zero amperes, or the converter can operate in discontinuous conduction mode DCM, in which the minimum inductor current can be zero amperes during a certain frequently switching period (Emerson et al, 2021;Philippe and Peter, 2020;Saravana et al 2014).…”
Section: Introductionmentioning
confidence: 99%